Preparation, Bandgap Engineering, and Performance Control of Graphene Nanoribbons - Luo, Hao; Yu, Gui (Chemistry of materials, 2022)
Graphene nanoribbons (GNRs) exhibit a series of essential electronic properties, especially in establishing tunable bandgaps. The bandgaps are determined by structural features of GNRs, including orientation, width, backbone/edge structure, heteroatom doping, and overall quality. These parameters affect the electronic properties of the GNRs to a large extent. To better incorporate GNRs into nanoscale electronic devices, obtaining high-quality GNRs with precisely defined bandgaps is a significant necessity. To date, different preparation techniques have offered a vast range of available materials for fabricating GNRs, where hydrocarbon gases and halogen-containing aromatic molecular precursors are the most important candidates. Therefore, it is fundamental to categorize the existing techniques in preparation, bandgap modulation, application of GNRs, and obtaining systematic knowledge on how to take advantage of this frontier material. Herein, overall understandings on the synthesis strategies and bandgap engineering tactics related to GNRs are presented in detail. Various techniques of top-down approaches and bottom-up syntheses, the origin of GNRs’ bandgap from quantum confinement effect, a diversity of bandgap engineering tools, and the applications of GNR-based devices are comprehensively reviewed with critical comparisons. In addition, the remaining challenges and promising opportunities are listed to catalyze upcoming findings pushing forward the ultimate applications of GNRs.